Control of Nanoparticle Size of Intrinsically Fluorescent PET (Polyethylene Terephthalate) Particles Produced Through Nanoprecipitation - Raffaella Lettieri; Muhammad Mudassir; Fabio Domenici; Andrea Salina; Mariano Venanzi; Cadia D’Ottavi; Elisabetta Di Bartolomeo; Emanuela Gatto (Molecules)
Plastics are widely produced due to their stability and ease of manufacturing, but many of them quickly become a waste, breaking down into microplastics and nanoplastics. While methods for the identification and characterization of plastic particles are well consolidated, the small size of nanoplastics presents challenges for their detection and analysis. Furthermore, due to the difficulty of identifying nanoplastics, analytical studies concerning their effect on cells and a comprehensive spectroscopic characterization are still lacking. In this paper, we overcome this obstacle by synthesizing and characterizing, for the first time, PET nanoparticles with specific, stable dimensions through a top-down approach. Using hexafluoroisopropanol-chloroform as a solvent, we prepared PET solutions at various concentrations and analyzed their spectral properties over time. Our results show that PET aggregates into nanoparticles, the quantity of which increases with concentration. These findings provide crucial insights for the detection of nanoplastics in environmental samples through fluorescence measurements and can potentially be used to produce stable PET nanoparticles to evaluate their cytotoxicity.